Comparative effect of resveratrol, carnosic acid and hernandulcin on target enzymes and biochemical markers linked to carbohydrate and lipid metabolism in mice - Villa-Ruano, Nemesio; Ramírez-García, Sergio Alberto; Landeta-Cortés, Gerardo; Cunill-Flores, José María; Horta-Valerdi, Guillermo M.; Hernández, Yesenia Pacheco (Emirates Journal of Food and Agriculture, 2023)
Resveratrol (RV), carnosic acid (CA) and hernandulcin (HE; a non-caloric sweetener) are envisioned as promising nutraceuticals to design new functional foods for improving lipid and carbohydrate metabolism. This study aimed to investigate the in vitro inhibitory effect of these molecules on specific enzyme targets and their capacity to improve distinctive markers associated to carbohydrate and lipid metabolism in murine model. The enzymes explored were alpha-amylase, alpha-glucosidase, and pancreatic lipase whereas ICR male mice were used for in vivo testing. Saturation curves (10-200 µM mL-1) and Lineweaver-Burk regressions suggested that RV, CA and HE exerts non-competitive inhibition on pancreatic lipase, alpha-glucosidase and alpha-amylase but, CA produced a strong competitive activity on alpha-amylase. RV was more effective to inhibit alpha-glucosidase (IC50, 22.1 µM) whereas CA was the most effective to inhibit both alpha-amylase (IC50, 11.7 µM) and pancreatic lipase (IC50, 31.5 µM). The effects of the oral administration of RV (300 mg/kg) HE (100 mg/kg) and CA (100 mg/kg) as well as the simultaneous administration of the three compounds at the same concentration was also explored in normoglycemic and diabetic mice. In addition, the prolonged administration of these substances combined with hypercaloric/atherogenic diet for 30 days was performed. Our results revealed a clear modulatory activity in both postprandial glucose and triglyceride levels as well an improvement in biochemical markers of mice treated with hypercaloric/atherogenic diet. The administration of HE produced a notable change (p < 0.01) in postprandial glucose assimilation at 60 min post-treatment in diabetic mice, whereas the other two compounds exerted a stronger depletion of glucose levels from 30 to 120 min post-treatment. A similar trend was recorded by RV and CA in postprandial triglyceride content, however, the latter compound was more effective (p < 0.05) at lower doses than RV. The simultaneous administration of the three compounds produced a significant improvement (p < 0.01) in biochemical parameters associated to carbohydrate (insulin and glucose) and lipid metabolism (total cholesterol, LDL-c, HDL-c, triglycerides, leptin, and adiponectin).Outstandingly, the mixture of the three compounds was more effective (p < 0.01) than the administration of sole compounds to amelioratethe side effects of the hypercaloric/atherogenic diet. Finally, the body weight of treated mice significantly decreased (from 5 to 20%; p < 0.05) in comparison with mice only fed with hypercaloric/atherogenic diet. Our results suggest that mixtures of RV, HE and CA may work better than their sole administration in mice and part of their biological activity could be associated with their inhibitory properties on the enzyme targets evaluated in this investigation. Keywords: Carnosic acid; Hernandulcin; Resveratrol; Hypoglycemic; Hypolipidemic; Murine model; Target enzymes